Production, characterization, and upgrading of waste tire pyrolysis oil for combustion applications (2021)
ABSTRACT: Waste tire (WT) valorization has gained significant impetus due to the rise in their pernicious disposal and subsequent environmental harm, coupled with the possibility of recovering both energy and materials. Rubber from WT (a mix of natural and synthetic rubber) exhibits high energy density (HHV 35 - 40 MJ/kg), high volatile matter content (55 - 65 wt.%), and a significant amount of carbon black (35 - 40 wt. %). Based on this composition, pyrolysis has been regarded as one of the pathways with a greater potential to recover both liquid and gaseous hydrocarbons, as well as valuable solid materials from WT. Hence, this thermochemical process has been perceived as a roadmap towards a circular and sustainable economy for WT management. In this scenario, this dissertation presents a comprehensive analysis, which starts highlighting the environmental and social issues related to WT, outlines their transformation into a valuable liquid fuel (tire pyrolysis oil) via pyrolysis in a twin-auger reactor using low-cost catalytic materials (CaO), and assesses distillation as an alternative for tire pyrolysis oil upgrading. In addition, the fuel and chemical properties of tire pyrolysis oil and its distillate fractions are studied from a fundamental point of view in order to provide new insights for their implementation in practical combustion applications, as well as for formulating further upgrading strategies. Finally, a model industrial pyrolysis plant is propose based on several experimental studies conducted at lab-scale and a thermoeconomic approach is taken in order to identify the benefits of scaling and modifying the process, as well as the potentials for improvement. In order to carried out this investigation, the initial part of this dissertation considered the study of the operational characteristics of a novel twin-auger reactor to transform WT by intermediate pyrolysis into tire pyrolysis oil (TPO), recovery carbon black (rCB), and tire pyrolysis gas (TPG). The influence of four operating parameters: reactor temperature (X1), WT mass flow rate (X2), solid residence time (X3) and N2 volumetric flow rate (X4), was assessed in order to maximize the TPO yield (Y1), while keeping the rCB one (Y2) as low as possible. The experimental campaign (thirty runs) was established according to the response surface methodology (RSM) based on a previously defined central composite design (CCD). The analysis of variance (ANOVA) showed that X1 and X2 exhibit the highest statistical influence on both Y1 and Y2. An optimization of both responses resulted in TPO, rCB, and TPG yields of 45, 40 and 15 wt.%, respectively, when the pyrolyzer is operated at 475 °C, 1.16 kg/h, 3.5 min and 300 mL/min. Furthermore, based on the optimum experimental conditions obtained by means of the RSM analysis, the repeatability of the experimental facility in terms of TPO, rCB, and TPG yields, as well as the consistency of the properties of the derived products were also assessed and discussed. Here, results of the ANOVA test aided at demonstrating that the experimental facility is repeatable in terms of TPO, rCB, and TPG yields. Moreover, the standard deviation calculated from the characterization of different product samples suggested that the physicochemical properties of TPO, rCB, and TPG obtained at given experimental conditions are also consistent. Thereafter, and going towards the upgrading of TPO, at the optimum experimental conditions, the effect of adding CaO during the pyrolysis of WT on the physiochemical properties of TPO, in particular sulfur content was assessed. As such, CaO was continuously fed at 10, 15, and 20 wt.%, based on a fixed WT mass flow rate (1.16 kg/h). The resulting TPO samples were initially characterized in terms of sulfur content. Then, the sample presenting the lowest sulfur content (TPO[CaO]) was further studied, along with the rCB and TPG related to TPO[CaO], named in this work rCB[CaO] and TPG[CaO], respectively. By adding CaO during the pyrolysis of WT, a maximum sulfur reduction in TPO of 26.40 wt.% was found. Moreover, CaO addition was also reflected on other physiochemical properties such as a reduction in the viscosity (from 2.6 to 1.9 cSt). Although the ash content of rCB[CaO] was significantly high after pyrolysis (57.5 wt.%), an acid demineralization step was effective at removing 80 wt.% of its inorganic content; in turn, this process improved rCB[CaO] surface area and porosity. Regarding TPG[CaO], an increase in the concentrations of H2 and some CxHy compounds (i.e. C3H8, C2H6, and C2H4), while a decrease in CO2, CO, and H2S ones confirmed the participation of CaO in several reactions during the pyrolysis of WT. Subsequently, this work pursued a comprehensive understanding of the structural characteristics of TPO and TPO[CaO]. Thereby, advanced analytical techniques such as Fourier Transform - Ion Cyclotron Resonance Mass Spectrometry (FT-ICR MS), and 1H and 13C Nuclear Magnetic Resonance (NMR) spectroscopy were utilized. FT-ICR MS results revealed the significant presence of pure hydrocarbons (HC) and hydrocarbons containing one sulfur atom (S1) in both fuels. HC compounds were found mainly in the form of tri-aromatics, tetra-aromatics, and penta-aromatics, while S1 compounds in the form of dibenzothiophene and benzonaphthothiophene (34 %). 1H and 13C NMR analysis showed that hydrogen atoms in methylene (CH2), methyl (CH3), and naphthenic groups, as well as hydrogen atoms in aromatic structures make up more than 80 % of both fuels. Similarly, carbon atoms in paraffinic groups (both CH2 and CH3) and protonated carbons in aromatic rings together form more than 50 % of the carbon atoms in TPO and TPO[CaO]. According to this characterization and considering the chemical complexity and wide boiling point range of TPO and TPO[CaO], distillation was perceived as an interesting alternative to group compounds with similar properties to be further refined and/or used in specific applications. Thus, the reduced sulfur TPO (TPO[CaO]) was further fractionated by distilled at atmospheric pressure into different fractions, named here light, low-middle, high-middle, and heavy. The structural characteristics of each fraction were also studied in-depth utilizing FT-ICR MS and NMR. Among others, fractionation by distillation resulted in concentration of both sulfur and highly aromatic compounds in the heaviest fraction. In addition to illustrating the structural features, the oxidation characteristics of TPO and TPO[CaO] as whole were investigated using non-isothermal thermogravimetric analysis. The thermogravimetric analyzer used in this study was coupled with a Fourier Transform Infrared (FT-IR) spectrometer, which allowed for obtaining valuable information regarding the real-time compositional changes of the evolved gases during the oxidation processes of both fuels, giving special attention to pollutants such as CO2, CO, SO2, NO. Furthermore, a comprehensive study into the oxidation characteristics of only the light fraction of TPO[CaO] obtained by distillation (named TPO[CaO]Light) was carried out by conducting combustion experiments in a jet stirred reactor (JSR) under a wide range of experimental conditions (i.e. temperatures and equivalence ratios). TPO[CaO]Light was chosen since it was the most abundant (40 vol.%) and it presented the lowest sulfur content among all of the distillate fractions. A surrogate fuel for TPO[CaO]Light was also formulated to facilitate future research into its combustion chemistry. Likewise, this surrogate fuel was tested in the JSR under the same experimental conditions used for TPO[CaO]Light in order to compare the reaction tendencies (i.e. fuel consumption rate) and the formation of main intermediate species. In this manner, it was possible to confirm if the proposed surrogate was a proper representation of TPO[CaO]Light. Roughly speaking, the information presented in this part of the research is fundamental for future investigations, for instance the development/adjustment of detailed kinetic mechanisms needed to model the combustion chemistry of the studied fuels. Finally, a thermoeconomic approach of a model WT pyrolysis plant at industrial scale with a nominal capacity of 1,000 kg/h was taken. This plant was proposed based on an exhaustive experimental campaign in a lab-scale twin auger reactor. Here, an exergy analysis was combined with the thermoeconomic principles to estimate the exergy and exergoeconomic cost of every stream in the process. Through this analysis, it was found that scaling and modifying the process can result in an increase in the plant’s exergy efficiency of around 20%, in contrast to the process conducted at lab-scale. In terms of monetary units, the production cost of TPO, rCB, and TPG was found to be 0.054 – 0.095 $/L, 0.035 – 0.062 $/kg, and 0.0082 – 0.012 $/kWh, respectively, depending on the feedstock (WT) price. Finally, an exergy decomposition analysis confirmed that 47 % of the exergy of TPO and TPG comes from renewable resources, namely NR. Therefore, their use as fuels is in line with the worldwide guidelines regarding the promotion of renewable energy, e.g. the 2009/28/EC European directive. In addition, 47 % of the energy of the combustion gases released into the atmosphere come from renewable resources, which implies reduced net carbon emissions. This could give rise to several benefits for this project, i.e. in terms of carbon credits.